Enhancing Creative Thinking through the Use of National Folklore in Visual Arts Education - Raxmonova Mahliyo Zoir qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of national folklore in visual arts education. It highlights how incorporating folk tales, traditional symbols, and cultural motifs in lessons fosters students’ creativity, aesthetic skills, and cultural awareness. The paper also examines pedagogical strategies for effectively integrating folklore into contemporary art education.